2014
DOI: 10.18585/inabj.v6i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Media of Human Umbilical Cord Blood Mesenchymal Stem Cell-derived Secretome Induced Apoptosis and Inhibited Growth of HeLa Cells

Abstract: BACKGROUND: Secreted factors contained in conditioned media (CM) of human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) known as secretome, was suspected to have important roles in regulating cells. This study was conducted to investigate the role of CM-hUCB-MSCs-derived secretome in apoptosis and growth of HeLa cells.METHODS: HeLa cells were treated with secretome in various concentrations (0, 0.2, 2 and 20%) for 24 and 48 hours. Trypan blue exclusion assay was performed to detect cell viability. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…(39) Meanwhile, in cancer research, modification on the microenvironment has also been reported. (40) Therefore, this potential strategy should be further investigated on ameloblastoma as well.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…(39) Meanwhile, in cancer research, modification on the microenvironment has also been reported. (40) Therefore, this potential strategy should be further investigated on ameloblastoma as well.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…Sub-G1 assay of apoptotic cells was performed as described by Sandra et al 14,15 Briefly, MG63 cells were treated with 0-10 μg/ml caffeic acid (Wako, Osaka, Japan) or chlorogenic acid (Wako, Osaka, Japan), harvested and suspended in 1 mL of hypotonic fluorochrome solution (50 μg/mL propidium iodide in 0.1% sodium citrate plus 0.1% Triton X-100). Cell suspension was placed at 4°C in the dark for 2 hours before the flow cytometric analysis.…”
Section: Sub-g1 Assaymentioning
confidence: 99%
“…Sub-G1 assay of apoptotic cells was performed as described by Sandra,et al(12,13) Briefly, MG63 cells were treated with 0-10 µg/ml caffeic acid (Wako, Osaka, Japan), harvested and suspended in 1 mL of hypotonic fluorochrome solution (50 µg/mL propidium iodide in 0.1 % sodium citrate plus 0.1 % Triton X-100). Cell suspension was placed at 4°C in the dark for 2 hours before the flow cytometric analysis.…”
Section: Sub-g1 Assaymentioning
confidence: 99%